Orgaan van de Vereeniging van Staatsmijnbeambten in Limburg. . Ons orgaan : tijdschrift van de Vereeniging van Staatsmijnbeambten in Limburg
Ook getiteld: Ons orgaan : tijdschrift van de Vereeniging van Staatsmijnbeambten in Limburg.